2017
DOI: 10.1016/j.jdiacomp.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The association of hyperglycemia and diabetes mellitus and the risk of chemotherapy-induced neutropenia among cancer patients: A systematic review with meta-analysis

Abstract: Aim Conduct a systematic review with meta-analysis to determine the association between incident chemotherapy-induced neutropenia (CIN) and either diabetes mellitus (DM) or hyperglycemia in patients with cancer. Methods Observational studies in cancer patients of any age receiving chemotherapy and having diabetes or hyperglycemia either during or before chemotherapy induction were included. Studies were retrieved by searching four databases (PubMed, EBSCO, ProQuest, and Cochrane) and cross-referencing. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
20
1
2
Order By: Relevance
“…Unlike previous research that suggested that receipt of chemotherapy may be associated with an increased risk of death (Alenzi & Kelley, 2017;Brunello, Kapoor, & Extermann, 2011;Crawford et al, 2008;Lega et al, 2013;Matias Cdo et al, 2013;Peairs et al, 2011), our findings revealed that chemotherapy was not associated with all-cause mortality after controlling for diabetes severity, cancer severity and all other possible covariates. This may indicate that the association between chemotherapy-related toxicity and mortality is mediated by diabetes severity since all the previous studies did not control for diabetes severity.…”
Section: Cancer Treatment and All-cause Mortalitycontrasting
confidence: 99%
“…Unlike previous research that suggested that receipt of chemotherapy may be associated with an increased risk of death (Alenzi & Kelley, 2017;Brunello, Kapoor, & Extermann, 2011;Crawford et al, 2008;Lega et al, 2013;Matias Cdo et al, 2013;Peairs et al, 2011), our findings revealed that chemotherapy was not associated with all-cause mortality after controlling for diabetes severity, cancer severity and all other possible covariates. This may indicate that the association between chemotherapy-related toxicity and mortality is mediated by diabetes severity since all the previous studies did not control for diabetes severity.…”
Section: Cancer Treatment and All-cause Mortalitycontrasting
confidence: 99%
“…Therefore, it is proposed that hyperglycemia may increase the risk of chemotherapy-induced neutropenia 14 . However, since hyperglycemia and diabetes are previously unrecognized as risk factors for chemotherapyinduced neutropenia, the collective evidence of their effect on developing chemotherapy-induced neutropenia during chemotherapy among patients with cancer needs further confirmation 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…CIN is specifically associated with older age, poorer functional and nutritional status, the presence of significant comorbidities, certain types of cancer, previous chemotherapy cycles, disseminated diseases, particular chemotherapy regimens, and combined therapy. Cancer patients with diabetes mellitus or hyperglycemia have a 32% higher chance of developing CIN than patients without these two conditions 12 .…”
Section: Biomarkers Of the Risk And Incidence Of Developing Cinmentioning
confidence: 99%